Synthesis and In Vitro Antimalarial Activity of Amino Chalcone Derivatives Compounds Through Inhibition of Heme Polymerization - Dona, Rahma; Jasril; Hendra, Rudi; Frimayanti, Neni (Fakultas Farmasi Universitas Andalas, 2024)
This study aims to investigate the potential of chalcone derivatives as antimalarial agents. The structure of the chalcone derivatives was designed by inserting amino substituents on acetophenone and methoxy variants on benzaldehyde to produce three amino chalcone derivatives (C1, C2, and C3). The synthesis was carried out by carrying out the Claisen-Schmidt condensation reaction with NaOH 40% as catalyst, resulting in compound yields ranging from 66% - 83%. The structure of the three compounds was determined by FTIR, MS, and 1H-NMR spectroscopy techniques, which confirmed that the compounds had structures that were in line with the desired molecular structure. The antimalarial activity test was carried out by inhibiting the heme polymerization process into hemozoin (β-hematin) using hydroxychloroquine sulfate as a positive control. Absorption measurements were carried out at two different wavelengths, namely 415 nm and 630 nm. The results of the IC50 antimalarial activity of the three compounds (C1, C2, C3) were obtained respectively at 227.61; 115.18; 260.01 µg/mL and positive control of 184.98 µg/mL. From these results, it was found that compound C2 showed better antimalarial activity compared to the other two compounds and positive control.